Efficacy and Safety of Umeclidinium Added to Fluticasone Propionate/Salmeterol in Patients with COPD: Results of Two Randomized, Double-Blind Studies. (2nd January 2016) - Siler, Thomas M.; Kerwin, Edward; Singletary, Karen; Brooks, Jean; Church, Alison
Abstract: Combinations of drugs with distinct and complementary mechanisms of action may offer improved efficacy in the treatment of chronic obstructive pulmonary disease (COPD). In two 12-week, double-blind, parallel-group studies, patients with COPD were randomized 1:1:1 to once-daily umeclidinium (UMEC; 62.5 μg and 125 μg)  or placebo (PBO), added to twice-daily fluticasone propionate/salmeterol (FP/SAL; 250/50 μg). In both studies, the primary efficacy measure was trough forced expiratory volume in 1 second (FEV1 ) at Day 85. Secondary endpoints were weighted-mean (WM) FEV1 over 0–6 hours post-dose (Day 84) and rescue albuterol use. Health-related quality of life outcomes (St. George's Respiratory Questionnaire [SGRQ] and COPD assessment test [CAT]) were also examined. Safety was assessed throughout. Both UMEC+FP/SAL doses provided statistically significant improvements in trough FEV1 (Day 85: 0.127–0.148 L) versus PBO+FP/SAL. Similarly, both UMEC+FP/SAL doses provided statistically-significant improvements in 0–6 hours post-dose WM FEV1 versus PBO+FP/SAL (Day 84: 0.144–0.165 L). Rescue use over Weeks 1–12 decreased with UMEC+FP/SAL in both studies versus PBO+FP/SAL (Study 1, 0.3 puffs/day [both doses]; Study 2, 0.5 puffs/day [UMEC 125+FP/SAL]). Decreases from baseline in CAT score were generally larger for both doses of UMEC+FP/SAL versus PBO+FP/SAL (except for Day 84 Study 2). In Study 1, no differences in SGRQ score were observed between UMEC+FP/SAL and PBO+FP/SAL; however, in Study 2, statistically significant improvements were observed with UMEC 62.5+FP/SAL (Day 28) and UMEC 125+FP/SAL (Days 28 and 84) versus PBO+FP/SAL. The incidence of on-treatment adverse events across all treatment groups was 37–41% in Study 1 and 36–38% in Study 2. Overall, these data indicate that the combination of UMEC+FP/SAL can provide additional benefits over FP/SAL alone in patients with COPD.